2001
DOI: 10.1016/s0022-1996(00)00090-8
|View full text |Cite
|
Sign up to set email alerts
|

Trade, wages, and ‘superstars’

Abstract: We study the e¤ects "globalization" on wage inequality. Our "global" economy resembles Rosen (1981) "Superstars" economy, where a) innovations in production and communication technologies enable suppliers to reach a larger mass of consumers and to improve the (perceived) quality of their products and b) trade barriers fall. When transport costs fall, income is redistributed away from the non-exporting to the exporting sector of the economy. As the latter turns out to employ workers of higher skill and pay, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 14 publications
4
96
0
Order By: Relevance
“…12 Casavola et al (1996) consider a large panel of firms between 1986 and 1990, finding that technological change explains most of the increase in relative skilled employment. More recently, Manasse et al (2001) analyze a panel of metal-mechanical firms observed from 1992 to 1995 and find that skill-biased technical change is the main determinant of skill upgrading. 13 The study also finds that trade has dampened the effects of technology on wage differentials, as employment has shifted towards unskilled-intensive firms (see also Faini et al (1999)).…”
Section: Technology Trade and Wagesmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Casavola et al (1996) consider a large panel of firms between 1986 and 1990, finding that technological change explains most of the increase in relative skilled employment. More recently, Manasse et al (2001) analyze a panel of metal-mechanical firms observed from 1992 to 1995 and find that skill-biased technical change is the main determinant of skill upgrading. 13 The study also finds that trade has dampened the effects of technology on wage differentials, as employment has shifted towards unskilled-intensive firms (see also Faini et al (1999)).…”
Section: Technology Trade and Wagesmentioning
confidence: 99%
“…Unlike the standard approach, our methodology allows us to identify the respective contributions of annual wages and employment to the change in the wage bill share. Moreover, our approach provides direct information on the changes of relative wages (see also Manasse et al, 2001).…”
Section: Firm-level Decompositionsmentioning
confidence: 99%
“…10 For a theoretical explanation of this evidence see Manasse and Turrini (2001). ics occurring at the level of individual firms and establishments, and thus have largely underestimated the role of demand and trade. At the theoretical level, trade theorists have argued that what matters for factor prices (in a two-sector two-factor Heckscher-Ohlin economy) is the sector in which technical progress occurs, rather than its factor bias (see e.g.…”
Section: Technology Trade and Wagesmentioning
confidence: 99%
“…12 Casavola et al (1996) consider a large panel of firms between 1986 and 1990, finding that technological change explains most of the increase in relative employment. More recently, Manasse et al (2001) analyze a panel of metal-mechanical firms and find that skill-biased technical change is the main determinant of skill upgrading, raising wage inequality within skilled workers (i.e. between managers and clerks) more than between manual and non-manual workers.…”
Section: Technology Trade and Wagesmentioning
confidence: 99%
See 1 more Smart Citation